Benchmarking in business through talents: beyond the success in motorsports - Syarizal Abdul Rahim; Norailis Ab. Wahab (2013)
In today‟s business environment, talent has become the potentially powerful source of competitive advantage. It is the fundamental building block to creating an organization which is capable of learning, innovating and changing, as well as executing new processes. It has been said that, talent management include the additional management processes and opportunities put in place for people in the organization that are considered to be talented. This paper intends to present a guide for racers to drive their companies by extending their success on the race tracks into business. This piece of work is based on the information gathered through in-depth interviews with three business owners that are also active racers. In the course of the interview, feedbacks regarding benchmarking through talent in motorsports and businesses were sought. The importance of talent management as seen through the prism of how top performers in motorsports have succeeded in driving their business while still producing impressive results on the race tracks was established in this study.